Getting a Foot on the Housing Ladder: The Role of Parents in Giving a Leg-Up - Elin Halvorsen; Kjersti-Gro Lindquist (Norges Bank, 2017)
In this paper we question whether parental resources are important for first-time buyers? We find a nuanced set of results. First, when parents help out financially, it clearly increases the probability of entering the housing market. Furthermore, some of this help is taken out as lower loan-to-value (LTV) and higher house value, and thus gives a head start on the rungs of the housing ladder. On the other hand, own income is economically much more important for first-time buyers than the potential or implicit help through having wealthy parents. Second, along with a growing gap between income and house prices, parental resources have become more important. Homeownership rates for young households with wealthy parents, or parents helping out financially, are increasing relative to young households without wealthy parents. We find no effect on the age of first entry into the housing market, which has declined for all young buyers, or on housing wealth inequality. Finally, we do not find that recent prudent mortgage-lending practices has caused a decline in the probability of entering the housing market, even for those who do not receive financial help from parents. We conclude that in a country like Norway, where there are well functioning credit markets and high intergenerational mobility, homeownership is still achievable without parental help, even under unfavorable conditions.
hdl:11250/2495558
Keywords: D64; D91; G28; R21; 330; inter vivos gifts; altruism; housing investment; debt